2‐Pyridinyl Thermolabile Groups as General Protectants for Hydroxyl, Phosphate, and Carboxyl Functions. Issue 1 (2nd March 2017) - Brzezinska, Jolanta; Witkowska, Agnieszka; Kaczyński, Tomasz P.; Krygier, Dominika; Ratajczak, Tomasz; Chmielewski, Marcin K.
Abstract: Application of 2‐pyridinyl thermolabile protecting groups (2‐PyTPGs) for protection of hydroxyl, phosphate, and carboxyl functions is presented in this unit. Their characteristic feature is a unique removal process following the intramolecular cyclization mechanism and induced only by temperature rise. Deprotection rate of 2‐PyTPGs is dependent on certain parameters, such as solvent (aqueous or non‐aqueous medium), pH values, and electron distribution in a pyridine ring. The presented approach pertains not only to protecting groups but also to an advanced system of controlling certain properties of 2‐pyridinyl derivatives. We improved the "chemical switch" method, allowing us to regulate the protecting group stability by inversing the electron distribution in 2‐PyTPG. Together with pH values manipulation, this allows us to regulate the protecting group stability. Moreover, phosphite cyclization to oxazaphospholidine provides a very stable but easily reversible tool for phosphate protection/modifications. For all TPGs we confirmed their utility in a system of protecting groups. This concept can contribute to designing the general protecting group that could be useful in bioorganic chemistry. © 2017 by John Wiley & Sons, Inc.